Corpus Inscriptionum Iudaeae/Palaestinae III: A Review - Gathercole, Simon J. (Journal for the study of the New Testament, 2015)
This review covers the third volume of the Corpus Inscriptionum Iudaeae/Palaestinae with special reference to its relevance to the study of the New Testament. This review follows the review published in JSNT in 2013 of the ﬁrst two volumes.